Analisis Pengaruh Ukuran Perusahaan dan Pertumbuhan Penjualan Terhadap Hutang Jangka Panjang Pada Perusahaan-Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2013 - Hardiyanto, Arief Wahyu, Imronudin, S.E, M.Si, Ph.D (2015)
This research aims to analyze the effect of the size of the company and sales growth partially or simultaneously against long term debt at telecommunications companies were listed on the Indonesia stock exchange. The population in this research is all the telecommunications companies were listed on the Indonesia stock exchange for the period 2009-2013, amounting to as much as 7 companies. Source data from a secondary data, i.e. data obtained from telecommunication company financial reports documentation published in the Capital Market Directory in 2009-2013. The research of using multiple linear regression test (test t test, F test, and R2). This research produced some findings. The results of the analysis of the coefficient of determination Adjusted R Square value obtained = 0.340 means a variation of independent variables consisted of company size and sales growth of 37,9% was able to explain the dependent variable i.e. varaiasi long-term debt at telecommunications companies were listed on the Indonesia stock exchange, while the rest (100%-37,9%) = 62,1% are influenced by factors other than the variables examined. The size of the company and sales growth simultaneously effect significantly to variable i.e. long term debt at telecommunications companies were listed on the Indonesia stock exchange, shown with probability value 0.000 of value 0.05 F < calculate 9.747. The Size of the company's positive and significant effect against long-term debt at Telecommunications Companies were listed on the Indonesia Stock Exchange, indicated by the value of the count of 4.403 t with probability value 0.000 of < 0.05. influential positive sales growth is not significantly to long-term debt at Telecommunications Companies were listed on the Indonesia Stock Exchange, indicated by the value t calculate of 0.540 with probability value of 0.593 > 0.05.